Assessing Fiscal Space in Sub-Saharan Africa - Calderon, Cesar; Chuhan-Pole, Punam; Some, Yirbehogre Modeste (World Bank, Washington, DC, 2018)
This paper presents new empirical evidence on how fiscal space in Sub-Saharan Africa has evolved over the past 15 years. Fiscal space is a multi-dimensional concept that is proxied by indicators capturing aspects of fiscal sustainability, balance sheet vulnerabilities, external debt positions, and market perception. The analysis relies on a new comprehensive database developed on a wide array of indicators (28) for a large set of countries in the world—of which 48 are in Sub-Saharan Africa. The analysis finds that, breaking with history, Sub-Saharan African countries were able to conduct countercyclical policies amid the 2008–09 global financial crisis, thanks to built-up liquidity and policy buffers. The evidence shows that fiscal adjustment efforts in the region were reversed amid the 2014–16 plunge in commodity prices, and oil and minerals and metals exporters saw a sharp deterioration in their primary balance sustainability gap. The paper finds a great deal of heterogeneity in the post–global financial crisis evolution of the fiscal space in the region. In countries with reduced fiscal space, the increase in the number of tax years to repay the debt fully was 1.1 years for the representative country, and in over one-third of the countries, this increase was more than one standard deviation above the median.